2016
DOI: 10.1177/0899764015597784
|View full text |Cite
|
Sign up to set email alerts
|

Does Motivation Matter for Employer Choices? A Discrete-Choice Analysis of Medical Students’ Decisions Among Public, Nonprofit, and For-Profit Hospitals

Abstract: Physicians are crucial resources for medical service provision, and aggravated physician shortages enhance the need to understand employer preferences and thus perceived employer attractiveness. Our study analyzes how differences in individual motivational factors explain intentional employer choice in the hospital industry. This study focuses on medical students who are faced with their first employer selection. Using a large-scale survey of medical students (n = 563) in Germany, we analyze these choices usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…Another limitation is that much of the literature on secondary trauma referenced in this article pertains to organizations in fields of activity (e.g., schools, hospitals, and social work clinics) that can be located in HSOs that are either nonprofit, private, or public. Research has found that organizations in the same field of activity in distinct sectors can be differentially construed by staff (for instance, hospitals; Winter & Thaler, ). Future research might unpack how these distinct perceptions elaborate the effectiveness of LEM behaviors in HSOs belonging specifically to the nonprofit sector.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that much of the literature on secondary trauma referenced in this article pertains to organizations in fields of activity (e.g., schools, hospitals, and social work clinics) that can be located in HSOs that are either nonprofit, private, or public. Research has found that organizations in the same field of activity in distinct sectors can be differentially construed by staff (for instance, hospitals; Winter & Thaler, ). Future research might unpack how these distinct perceptions elaborate the effectiveness of LEM behaviors in HSOs belonging specifically to the nonprofit sector.…”
Section: Discussionmentioning
confidence: 99%
“…Nonprofit employees experience unique organizational environments, potentially value social rewards over economic rewards, and potentially value the organizational mission over the organization itself (De Cooman et al, 2011, Schepers et al, ), and many authors discuss differences between for‐profit and nonprofit workers in areas such as job satisfaction (Y. Lee, ), motivation, and job choice (Winter & Thaler, ). Thus, well‐known management concepts can manifest in unique ways, and our results may be tied exclusively to nonprofit employment.…”
Section: Discussionmentioning
confidence: 99%
“…These students are expected to be looking for a job in the coming months. In order to include a variety of students regarding curriculum orientation, as suggested by Winter and Thaler (), we obtained their email addresses from four faculties of our university. They then received an email with an electronic link to the survey.…”
Section: Methodsmentioning
confidence: 99%